La obtención indebida de la prueba en los procesos penales y su violación a las garantías constitucionales - Pacheco Barrera, Elina Gabriela (2015)
The research was conducted in the city of Quevedo with the objective of legal base and doctrinally a training system that set the level of application of due process in the evaluation of evidence by judges in criminal proceedings to ensure respect for the constitutional rights of the people involved. Answer polls closed to 369 residents of Canton and 30 lawyers, were carried out the survey had five questions for each entity. The results indicate that 75% of respondents inhabitants, ignore what is improper evidence in judicial proceedings. They also do not know the system of due process in the prosecution of crimes must be ensured by the presentation of evidence. 83% do believe that constitutional rights have been violated to present evidence then determine improper or illegal. Consequently, 83% of respondents state that the undue test violates due process. While 77% of professionals considered that judges must be trained to correctly perform the assessment of the evidence. Similarly, 70% believe that the presentation of illegal evidence at trial produces legal uncertainty. In addition, 73% believe that would violate criminal and constitutional guarantees of those who may be affected by the improper taking of evidence in litigation. In conclusion, the doctrinal and legal analysis about the improper obtaining evidence indicates that under no circumstances should be violated constitutional rights and guarantees, to be violated due process and hence the rights and constitutional guarantees for individuals.